2020
DOI: 10.1007/s40801-020-00196-6
|View full text |Cite
|
Sign up to set email alerts
|

Expediting Discharge in Hospitalized, Adult Patients with Skin and Soft Tissue Infections Who Received Empiric Vancomycin Therapy with Oritavancin: Description of Findings from an Institutional Pathway

Abstract: Background An internal quality assurance review at AtlantiCare Regional Medical Center (ARMC) revealed that patients admitted with skin and soft tissue infections (SSTIs) remained in hospital post-resolution of acute symptoms and demonstrated a delayed transition to step-down oral antibiotic therapy. A non-mandatory institutional pathway was developed and implemented in 2016 to expedite hospital discharge in hemodynamically stable SSTI patients by utilizing oritavancin. Objective To describe the outcomes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…Many patients with ABSSSIs, including those with minimal comorbidity and mild or no systemic signs of infection, are hospitalized for several days solely to receive multi-dose and multi-day parenteral antibacterial therapy, which poses a significant financial burden on healthcare systems [5][6][7]. Based on any comorbidities and infection severity, hospitalized patients receiving multi-dose and multi-day parenteral antibacterial therapy may transition to outpatient parenteral or oral antibacterial therapy (OPAT) [7,8].…”
Section: What Are the Antibacterial Effects Of Oritavancin?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with ABSSSIs, including those with minimal comorbidity and mild or no systemic signs of infection, are hospitalized for several days solely to receive multi-dose and multi-day parenteral antibacterial therapy, which poses a significant financial burden on healthcare systems [5][6][7]. Based on any comorbidities and infection severity, hospitalized patients receiving multi-dose and multi-day parenteral antibacterial therapy may transition to outpatient parenteral or oral antibacterial therapy (OPAT) [7,8].…”
Section: What Are the Antibacterial Effects Of Oritavancin?mentioning
confidence: 99%
“…To improve patient clinical outcomes and resource utilization, several centres in the USA have implemented oritavancin as part of a multidisciplinary treatment program for ABSSSIs [12]. Indeed, real-world studies have suggested potential clinical and economic benefits associated with the single-dose IV oritavancin regimen in patients with ABSS-SIs where the treatment reduced disease progression rates [6], infection sequelae from ABSSSI treatment failures [35], 30-day hospital readmission rates [6,35,36] and/or length of hospital stays without affecting readmission rates [5,6]. Furthermore, pharmacoeconomic analyses (from the hospital perspective) of oritavancin versus vancomycin in patients with confirmed or suspected gram-positive ABSSSIs and risk of MRSA in the USA indicate that oritavancin is associated with substantial healthcare cost savings by lowering drug administration burden and reducing hospital admissions [37,38].…”
Section: What Is the Current Clinical Position Of The New IV Formulat...mentioning
confidence: 99%
“… 126 This finding appears to be confirmed by the results of a descriptive retrospective cohort of adult inpatients with SSTIs who were discharged with single-dose oritavancin or oral step-down antibiotic therapy, revealing fewer 30 day SSTI-related readmissions in patients receiving oritavancin 7/99 (7.1%) compared with 18/100 (18.0%) with oral step-down therapy; 6 of the 7 readmissions in patients receiving oritavancin involved Gram-negative pathogens. 127 Meanwhile, a retrospective real world study comparing single-dose dalbavancin to standard of care in age- and BMI-matched adults with ABSSSI revealed more 30 day SSTI-related readmissions in patients treated with dalbavancin 55/209 (26.32%) compared with standard of care 31/209 (14.83%; P < 0.01). 128 …”
Section: Phase III Studies With Lipoglycopeptidesmentioning
confidence: 99%
“…Four studies (Estrada et al [15], Whittaker et al [16], Helton et al [17], and Brownell et al [18]) report observations from real-world clinical settings in terms of either avoidance of hospitalization or early discharge from an inpatient setting by use of single-dose oritavancin for treatment of ABSSSI. Oritavancin was administered in outpatient parenteral antimicrobial therapy programs, emergency departments (EDs), or last day hospital stays in a total of 451 patients with ABSSSI.…”
mentioning
confidence: 99%
“…Importantly, these studies were undertaken following identification of patients in their respective institutions who remained hospitalized solely for the purpose of parenteral antibiotic therapy despite clinical stability with significant infection resolution of ABSS-SIs. The value of internal quality assurance review is a key characteristic of the study by Whittaker et al [16] in devising programs that can lower healthcare costs. Overall, the ABSSSI-focused studies reveal methodologies that may be implemented by a variety of healthcare institutions to achieve early and directed patient discharge and calculate cost savings associated with hospital days prevented.…”
mentioning
confidence: 99%